2019
DOI: 10.1016/j.ijfoodmicro.2019.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes isolates from ready to eat plant produce are diverse and have virulence potential

Abstract: Listeria monocytogenes is sporadically detected on a range of ready to eat fresh produce lines, such as spinach and rocket, and is a threat to public health. However, little is known about the diversity of L. monocytogenes present on fresh produce and their potential pathogenicity. In this work, fifteen Listeria monocytogenes isolates from the UK fresh produce supply chain were characterised using whole genome sequencing (WGS). Additionally, isolates were characterised based on their ability to form biofilm. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…This sequence type has, however, frequently been found to dominate in raw pork meat ( 21 , 52 , 61 ) and is also commonly found to persist in slaughterhouses ( 14 , 15 , 24 , 62 ) as well as in downstream compartments in the meat processing chain ( 10 , 22 , 26 ). In contrast, several studies report an absence or low abundance of ST9 in other food types and processing environments, such as fish/salmon, dairy, and fresh produce ( 22 , 26 , 31 , 47 , 63 ). These observations suggest that ST9 isolates are highly adapted to survival in meat production environments.…”
Section: Discussionmentioning
confidence: 94%
“…This sequence type has, however, frequently been found to dominate in raw pork meat ( 21 , 52 , 61 ) and is also commonly found to persist in slaughterhouses ( 14 , 15 , 24 , 62 ) as well as in downstream compartments in the meat processing chain ( 10 , 22 , 26 ). In contrast, several studies report an absence or low abundance of ST9 in other food types and processing environments, such as fish/salmon, dairy, and fresh produce ( 22 , 26 , 31 , 47 , 63 ). These observations suggest that ST9 isolates are highly adapted to survival in meat production environments.…”
Section: Discussionmentioning
confidence: 94%
“…Last but not least, pathogenicity is a multifactorial process, and cannot merely be derived from the presence or absence of virulence genes [39]. In summary, the variety of potentially pathogenic strains circulating at the producer, as already described in other food processing plants [40], clearly shows that selectively removing the source of contamination for one specific outbreak cluster is neither sufficient nor sustainable. Instead, the entire L. monocytogenes population in a food processing plant must be controlled and eliminated to not only stop present outbreaks but to also prevent future ones.…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, not all L monocytogenes strains are equally virulent; some strains are highly virulent and are more often associated with epidemics, while others are less virulent and are infrequently related to epidemics. [1][2][3] Previous studies have shown that lineage I (or ST 4b) occurs more frequently among clinical isolates than lineage II (or ST 1/2b, ST 1/2a and ST 1/2 c), relative to the frequency of these categories in food. 4 Besides intrinsic L monocytogenes virulence, other extrinsic factors play an equally important role in listeriosis outbreaks, such as individual susceptibility, food category, good hygiene practices and good manufacturing practices, and persistence into the environment or biofilm formation, among others.…”
Section: Discussionmentioning
confidence: 99%
“…32 Understanding the virulence aspects of L monocytogenes in animals and food supply chains can help regulators and operators design more effective microbial surveillance and prevention strategies. 1 In this sense, more strict control measures, such as a lower limit of bacterial load in food, could be implemented when especially virulent L monocytogenes strains are identified. In the present study, the issue of the general virulence potential of L monocytogenes strains from pig samples in Spain was addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation